Chemo-surgical approach in vulvar leiomyosarcoma: A case report. Issue 6 (December 2022) - Capalbo, Giuseppe; Logoteta, Alessandra; Gallo, Roberta; Cuccu, Ilaria; Gentile, Gabriella; Arienzo, Francesca; Musella, Angela; Pernazza, Angelina; Perniola, Giorgia; Di Donato, Violante; Manganaro, Lucia; Bogani, Giorgio; et al.
Introduction: Primary sarcoma of the vulva is an extremely rare entity, representing only 1%–3% of all vulvar malignant neoplasms. Among sarcomas, leiomyosarcoma (LMS) is the most prevalent histologic variant. Due to the rarity of LMS, guidelines are lacking and phase III trials have not been carried out, so clinical management is based on local clinical practice and physician experience. Case presentation: Here, we described a case of primary LMS of the vulva and its successful management, with the adoption of neoadjuvant chemotherapy and surgery. We report a case of a 74-year-old woman with 12.5 cm vulvar LMS. The patient received three cycles of neoadjuvant chemotherapy with a partial response. Radical vulvectomy with vulvar reconstruction with V-F flap was carried out. Surgical margins were negative. Three additional cycles of adjuvant chemotherapy were delivered. Results: One year after treatment, the patient was disease-free. Conclusion: There are no approved therapeutic protocols for this rare neoplasia. Surgery is the mainstay of treatment. However, it is not always feasible, so neoadjuvant chemotherapy was delivered for downstaging the vulvar lesion. We suppose that neoadjuvant chemotherapy has optimized the possibilities of radical surgery. Despite the anectodical nature of this case presentation, neoadjuvant chemotherapy seems a valid therapeutic option for managing patients with bulky vulvar sarcoma. Further large collaborative studies are warranted to identify the best therapeutic option for these patients.